MANAGEMENT OF GENITAL WARTS THROUGH AYURVEDA-A CASE REPORT - Surendran, *Emy S; T P, Sinimol; G N, Sreedeepthi (International Journal of Ayurveda and Pharma Research, 2019)
External genital warts or Condyloma Acuminata is caused by the Human Papilloma Virus subtypes 6 and 11. According to Ayurveda it can be diagnosed as Yoni Arsa. This case report presents a 51 yr old female with the complaints of per vaginal discharge, itching and appearance of progressively increasing number of lesions in the vulva for 6 months. The pathological diagnosis of the vulvar lesion specimen was Condyloma Acuminata. Patient was treated with internal administration and external application of Ayurvedic medicines. Considerable relief for the condition was noted and the follow up visits confirmed the non recurrence of the disease. Ayurvedic interventions can be considered as minimal invasive and cost effective in the management of genital warts.